Biocontrol activity and action mechanism of Paenibacillus polymyxa strain Nl4 against pear Valsa canker caused by Valsa pyri - Yuan, Hongbo; Yuan, Mengjia; Shi, Bingke; Wang, Zhuoni; Huang, Tianxiang; Qin, Genhong; Hou, Hui; Wang, Li; Tu, Hongtao (Frontiers in Microbiology, 2022)
Pear Valsa canker caused by Valsa pyri is among the most destructive diseases of pear, which causes significant economic loss. The present study was developed to explore the biocontrol efficiency and underlying antagonistic mechanism of Paenibacillus polymyxa strain Nl4 against V. pyri. P. polymyxa strain Nl4, one of the 120 different endophytic bacterial strains from pear branches, exhibited strong inhibitory effects against the mycelial growth of V. pyri and caused hyphal malformation. Culture filtrate derived from strain Nl4 was able to effectively suppress mycelial growth of V. pyri, and was found to exhibit strong protease, cellulase and β-1, 3-glucanase activity. Through re-isolation assay, strain Nl4 was confirmed to be capable of colonizing and surviving in pear branch. Treatment with strain NI4 effectively protected against pear Valsa canker symptoms on detached pear twigs inoculated with V. pyri. Moreover, strain Nl4 promoted enhanced plant growth probably through the solubilization of phosphorus. Comparative transcriptomic analyses revealed that strain NI4 was able to suppress V. pyri growth in large part through the regulation of the expression of membrane- and energy metabolism-related genes in this pathogen. Further transcriptomic analyses of pear trees indicated that strain NI4 inoculation was associated with changes in the expression of genes associated with secondary metabolite biosynthesis, signal transduction, and cutin, suberine, and wax biosynthesis. Together, these data highlighted P. polymyxa strain Nl4 as a promising biocontrol agent against pear Valsa canker and investigated the possible mechanisms of strain Nl4 on control of this devastating disease.